Occupational stress, coping strategies, and mental health among clinical nurses in hospitals: a mediation analysis - Jin, Fubi; Ni, Shaomei; Wang, Lin (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to examine the relationship between occupational stress and mental health among clinical nurses, focusing on the mediating role of coping strategies.MethodsA cross-sectional survey was conducted among 600 clinical nurses from tertiary hospitals in Hangzhou, China. Data were collected using the Chinese Nurses’ Work Pressure Source Questionnaire, the Symptom Checklist-90 (SCL-90), and the Coping Strategies Scale. Mediation analysis was performed using Bootstrap to test the hypothesized mediating effects.ResultsThe results showed that occupational stress was positively associated with mental health issues (β = 0.42, p < 0.01), and coping strategies partially mediated this relationship (indirect effect = 0.18, 95% CI [0.11, 0.27]). Nurses in high-stress departments (e.g., surgery and ICU) reported significantly higher SCL-90 scores than the national norm (p < 0.05).ConclusionThe findings suggest that positive coping strategies can mitigate the adverse effects of occupational stress on mental health. Interventions targeting coping skills training may improve nurses’ well-being and reduce burnout.